2015
DOI: 10.1111/birt.12171
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance Transfer in Case of Postpartum Hemorrhage after Birth in Primary Midwifery Care in The Netherlands: A Prospective Cohort Study

Abstract: We found no relation between the duration of ambulance transfer and maternal condition or outcomes. All women fully recovered. The low-risk profile of women in primary care, well-organized midwifery, and ambulance care in The Netherlands are likely to contribute to these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, we highlighted a hospital random effect, suggesting that all the variables included in our analysis can explain on their own the difference in mothers' or newborn's outcome. A few variables, sometimes identified as relevant in the literature and not included in our model may explain this effect, such as mothers' origin, 44 newborn's birthweight, 10 the need of an ambulance transfer, 45 or even consideration of out-of-hospital deliveries. 46,47 Finally, our results are backed up by those of larger countries with a centralized organization than ours.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we highlighted a hospital random effect, suggesting that all the variables included in our analysis can explain on their own the difference in mothers' or newborn's outcome. A few variables, sometimes identified as relevant in the literature and not included in our model may explain this effect, such as mothers' origin, 44 newborn's birthweight, 10 the need of an ambulance transfer, 45 or even consideration of out-of-hospital deliveries. 46,47 Finally, our results are backed up by those of larger countries with a centralized organization than ours.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from travel time studies Description of included studies Fifteen studies explored the impact of travel time from a woman's home to an OU (see table 7). Two studies (one reported as an abstract only) were conducted in the UK, [29][30][31] three studies in France, [32][33][34] three studies (reported in five articles) in the Netherlands, [35][36][37][38][39] one study reported in two articles from Norway, 40 41 five studies in Canada [42][43][44][45][46] and one study in Japan. 47 Eleven studies were of a retrospective cohort design, one was a prospective cohort study, 39 one was a before-and-after design 47 and two were case-control studies.…”
Section: Hypoxic-ischaemic Encephalopathy (Hie)mentioning
confidence: 99%
“…Only singleton births were included in five studies. 30-32 35-38 42 One study 39 specifically enrolled women with postnatal haemorrhage after home birth, and one study 42 focused on planned home birth regardless of the actual place of birth.…”
Section: Hypoxic-ischaemic Encephalopathy (Hie)mentioning
confidence: 99%
See 1 more Smart Citation
“…Timeliness refers to the geographical distribution of resources, and the distance and time to reach them. As such, transportation is emphasized as essential to achieve timely care [62][63][64][65][66]. Availability of resources includes availability of expertise, facility, technology, diagnostics and therapy [67][68][69][70][71][72][73][74].…”
Section: Risk Selection As An Organisational Measure: Aligning Risk Amentioning
confidence: 99%